PERAN GURU KELAS DALAM MEMBENTUK KARAKTER SOPAN SANTUN ANAK DI SDN 5 MULYOHARJO JEPARA - Hanatin Latifah Pramono; Erik Aditia Ismaya; Wawan Shokib Rondli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to find out the teacher's role in shaping the polite character of children at SDN 5 Mulyoharjo Jepara. This study used narrative data analysis techniques, including the stages of observation, interviews, documentation and recording, by taking the subject of class teachers and students as research subjects. The important role of the teacher is to give examples of politeness, make class agreements, and provide restitution if the child speaks impolitely. Factors inhibiting the formation of polite character can be classified; 1. Unable to control children's behavior, (2) Students who do not respect elders, (3) Student delinquency. The solution that can be done is to look at the child's family background, advise him, and get used to polite behavior in class.